Rencana Strategis Klinik SS dalam Upaya Mewujudkan Keunggulan Bersaing (Competitive Advantage) - Rukhiyat Syahidin (SOSIOHUMANITAS, 2018)
Research is held at Clinic SS Bandung, using the applied theory of strategy management, a qualitative explorative approach study based on primary and secondary data which appear in descriptical method. Respondents were 50 patients of Clinic SS, which are selected using snowball sampling method. The result shows that at this time Clinic SS have many weaknesses that should be improved in order to get competitive advantage, also found several competitors around Clinic SS area that is more superior or equal to Clinic SS, also found inhibitory factors in order to achieve competitive advantage such as clinic management that have not done well, government policy which make patients tend to choose clinic which has a drugstore and BPJS service, and clinic’s management which is not efficient and effective.